Pelatihan Pembuatan Media Pembelajaran Menggunakan Canva Kepada Guru di MAM Talu - Afni Nia Sari; Elvira Sawitri; Rizalina (CV. ITTC INDONESIA, 2024)
In current technological developments, since the Covid-19 case occurred, a lot of learning has been done online and then after the cases started to improve, many schools are still implementing online learning. To increase students' interest in learning at school, a learning model is needed that attracts students' interest in learning, whether online or offline. One tool that can be used is canva1. Canva is a graphic design tool to help create creative designs that are easy to use. In this activity, training was carried out on making learning media using Canva for MAM Talu teachers. This activity aims to improve participants' abilities in creating learning media using Canva2. This activity consists of 3 stages, namely planning, implementation and evaluation and reporting. The implementation stage was carried out using interactive lecture and practice methods. The presentation of the material is continued with the practice of making learning media. This activity was attended by 25 MAM Talu teachers. After the training, all participants were able to create learning media3. Based on the survey, 16.13% strongly agreed, 45.16% of participants agreed, 29.03% disagreed and 9.68% disagreed with using Canva in creating learning media. This training activity was very useful and broadened participants' insight into creating learning media.